Establishment and management of field genebank: A training manual IPGRI-APO, Serdang - Saad, M.S.; Ramanatha Rao, V.; International Plant Genetic Resources Institute (2001)
Many important varieties of field, horticultural and forestry species are either difficult as their seeds, if produced, are recalcitrant or reproduce vegetatively. Genetic resources of such plant species are generally conserved in field genebanks. Despite the often-cited drawbacks, field genebanks provide easy and ready access to conserved material for research as well as for use. In addition, for a number of plant species the alternative methods have not been fully developed and hence the field genebanking is the most appropriate method. For species that have alternative methods, field genebank is still a major component of a complementary strategy for the conservation of their genetic resources. Despite the importance of field genebank in a plant genetic resources conservation system, the concepts and scientific principles for establishing and managing field genebanks are not very well understood by many workers. This Manual, based on a regional training course attempts to clarify most of such principles.The Manual introduces the principle and concepts of genetic resources conservation and shows the role of field genebank in a complementary conservation strategy that is required to conserve and use most of genetic diversity in any genepool. It deals with the current status of seed and in vitro and cryopreservation so that the role of field genebank would become clear in an ex situ conservation strategy for crop genepool. Some legal aspects are considered that need to be taken care of while establishing a field genebank. The question of what material should be conserved in field genebank is dealt in a chapter while the genetic principles underlying the accessions conserved a field genebank are elaborated in another. Practical aspects of laying out the field plots and planting are described. The simple but important considerations such as soil heterogeneity and interplant competition are considered. As noted earlier, the field genebank has a major role to play in characterization and evaluation, as it may be very difficult to plant another experiment in the case of a perennial species specifically for such purpose and the factors that need to be considered for combining the twin objectives, i.e. conservation and characterization are described. In addition, the material in a field genebank is readily available for utilization and how this utilization could be made without countermanding conservation role is discussed. In characterization and evaluation and utilization of genetic resources, modern biotechnology will play a major role and hence an introduction to biochemical markers is provided. Finally, any conservation effort should be cost effective to be sustainable and economics of conservation using field genebank are considered.